2015
DOI: 10.1097/md.0000000000000763
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Burden in the Hippocampus and Default Mode Network

Abstract: Amyloid load, as measured by florbetapir positron emission tomography (PET) standardized uptake value ratio (SUVr), has high specificity in the diagnosis of Alzheimer disease (AD). As the posterior cingulate cortex (PCC) represents densely amyloid-affected regions early in AD, we hypothesized that amyloid load within the key hubs of the default mode networks (DMN) may result in local or distant interconnected gray matter (GM) volume atrophy, thereby affecting cognitive performance. Thirty AD patients with a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 38 publications
1
18
1
Order By: Relevance
“…According to our NBS analysis, an altered subnetwork connection between LLD-MD and LLD-IM patients comprises the frontal, paralimbic, subcortical and some parietal and temporal regions, which are mainly involved in the right CCN and corticostriatal circuits as well as belonging to feeder and local connections, and the strength of this NBS's subnetwork is correlated with cognitive function in LLD groups. Different from other articles in brain structural change and memory, which show mainly difference in default mode network (Chang et al, 2015 ; Yin et al, 2016 ), our finding suggested that the memory deficits in LLD patients is relevant with the disruption of the right CCN and corticostriatal circuits. In the current study, this NBS's subnetwork is mostly belonging to feeder and local connections.…”
Section: Discussioncontrasting
confidence: 99%
“…According to our NBS analysis, an altered subnetwork connection between LLD-MD and LLD-IM patients comprises the frontal, paralimbic, subcortical and some parietal and temporal regions, which are mainly involved in the right CCN and corticostriatal circuits as well as belonging to feeder and local connections, and the strength of this NBS's subnetwork is correlated with cognitive function in LLD groups. Different from other articles in brain structural change and memory, which show mainly difference in default mode network (Chang et al, 2015 ; Yin et al, 2016 ), our finding suggested that the memory deficits in LLD patients is relevant with the disruption of the right CCN and corticostriatal circuits. In the current study, this NBS's subnetwork is mostly belonging to feeder and local connections.…”
Section: Discussioncontrasting
confidence: 99%
“… 30 Many brain-function areas are involved in the DMN, including the medial frontal, anterior cingulate, inferior temporal, posterior cingulate, precuneus, and inferior parietal regions, and these brain areas have always been the hot spot in the study of the default mode. 31 Several studies have shown dysfunction of the DMN in Parkinson’s disease, 32 Alzheimer’s disease, 33 schizophrenia, 34 and depression. 35 Toosy et al 36 found that patients with ON showed abnormal activation of areas in the posterior parietal and lateral temporal cortices, while Werring et al 37 reported similar findings in the lateral temporal and posterior parietal cortices and in the thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative evidence suggests the cingulate cortex is a hub that links multiple brain regions (Gong et al, 2009; Hagmann et al, 2008). By integrating input from various sources, such as hippocampus and prefrontal cortex, CC actively participates in the regulation of multiple cognitive functions as part of Papez circuit (or medial limbic circuit) (Papez, 1937; Shackman et al, 2011), and is disrupted early in both normal aging and AD-associated neurodegeneration (Chang et al, 2015; Sheline et al, 2010). Such characteristics make CC an ideal region for understanding the influence of functional connectivity (FC) on excellent memory, by connecting to the hippocampal and prefrontal regions.…”
Section: Introductionmentioning
confidence: 99%
“…Such characteristics make CC an ideal region for understanding the influence of functional connectivity (FC) on excellent memory, by connecting to the hippocampal and prefrontal regions. Furthermore, compared to other brain regions, including medial temporal/hippocampal and prefrontal lobes, CC is affected by amyloid deposition early in both aging and AD (Camus et al, 2012; Chang et al, 2015; La Joie et al, 2012). Notably, in an emerging structural imaging study examining the default neural networks, cortical thickness was preserved in multiple cingulate, hippocampal, and frontal regions among Supernormals when compared to their younger counterparts (Sun et al, 2016).…”
Section: Introductionmentioning
confidence: 99%